The Institution of Ribat Under the Sokoto Caliphate and its Relevance to Contemporary Muslims - Tambari Abbas Bashar (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study explores the role of the Ribat institution within the Sokoto Caliphate, a significant Islamic empire in 19th-century West Africa. The research aims to analyze the historical context, functions, and impact of Ribat in the spread of Islam, Islamic education, and the defence of Muslim territories. Given the centrality of the Sokoto Jihad in transforming the socio-political and intellectual landscape of Hausaland and beyond, the study particularly examines how Ribat contributed to the development of learning and scholarship, making knowledge an essential tool in Islamic propagation. Theoretical Framework: The theoretical framework of this study is based on the concept of Islamic governance and educational institutions in classical and modern Islamic thought. It highlights the role of fortified religious centres in sustaining Islamic civilizations and their function as hubs of learning and social cohesion. Literature Review: A review of the literature includes prior studies on the Sokoto Jihad, the establishment of the Sokoto Caliphate, and the role of Ribat in Islamic history. Previous research has largely focused on the political and military aspects of the Jihad, with limited attention to the institutional development of Ribat and its intellectual contributions. This study seeks to fill this gap by analyzing Ribat’s role beyond military defence, particularly its influence on Islamic education and community development. Methods: The research employs a historical and analytical approach, utilizing primary sources such as manuscripts from Sokoto scholars and secondary sources on Islamic governance in West Africa. Through qualitative analysis, the study reconstructs the historical significance of Ribat and evaluates its implications for contemporary Muslim societies. Results: Findings reveal that Ribat played a crucial role in the dissemination of Islamic knowledge, strengthening Muslim identity, and ensuring the security of the Islamic state. It functioned as both a centre of learning and a defensive stronghold, reinforcing the Caliphate’s intellectual and religious authority. Implications: The study’s implications highlight the need for modern Muslim communities to revisit and adapt the Ribat model in addressing contemporary challenges, particularly in the fields of Islamic education, community empowerment, and faith preservation. Novelty: The novelty of this research lies in its comprehensive examination of Ribat beyond its conventional military function, positioning it as a cornerstone of Islamic intellectual and social development. This perspective contributes to the broader discourse on the historical and modern relevance of Islamic institutions.